Photoluminescence properties and thermal stability of samarium-doped barium phosphate phosphors. Issue 5 (1st April 2017) - Chiang, Chung-Hao; Fang, Ying-Chien; Lin, Han-Yu; Chu, Sheng-Yuan
Abstract: In this paper, Sm 3+ -doped Ca6 BaP4 O17 phosphors were synthesized via a conventional solid-state reaction method. Orange-red emission was observed from these phosphors under near-ultraviolet (UV) excitation at 405 nm. The luminescence properties of the obtained phosphors were characterized. The Ca6 BaP4 O17 :Sm 3+ phosphor can be efficiently excited by near-UV and blue light, and their emission spectrum consists of three emission peaks, at 567, 602, and 650 nm, respectively. The thermal stability of Ca6 BaP4 O17 :Sm 3+ phosphors was investigated systematically and corresponding mechanisms were proposed. Based on the results, the as-prepared Ca6 BaP4 O17 :Sm 3+ phosphors are promising orange-red-emitting phosphors for near-UV-based white light-emitting diodes.